2006
DOI: 10.1089/aid.2006.22.1242
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriately Low Glycated Hemoglobin Values and Hemolysis in HIV-Infected Patients

Abstract: In order to test the accuracy of glycated hemoglobin (HbA1c) in predicting mean glycemia in HIV-infected patients, we recorded consecutive HbA1c measurements from 1238 non-HIV-infected and 112 HIV-infected patients, all devoid of any hemoglobinopathy, in a retrospective, transversal study. Mean fasting glycemia from the six previous weeks (measured-Gly) and HbA1c-estimated glycemia [HbA1c-Gly (1.85x%HbA1c-4.78) mM] were compared. Mean hemoglobin, red cell volume, serum creatinine, CD4 count, and HIV viral load… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
58
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 19 publications
8
58
0
1
Order By: Relevance
“…The potential consequences of these results must be analyzed with respect to the high incidence of diabetes and/or insulin resistance in the HIV-infected population (44,45). Furthermore, several studies have already shown the accumulation of circulating AGEs in HIV-infected patients, with or without metabolic syndromes (17)(18)(19). Circulating AGEs likely interact with their receptor RAGE in lymphocytes, monocytes/ macrophages, and DCs that are also targets and/or reservoirs of HIV-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential consequences of these results must be analyzed with respect to the high incidence of diabetes and/or insulin resistance in the HIV-infected population (44,45). Furthermore, several studies have already shown the accumulation of circulating AGEs in HIV-infected patients, with or without metabolic syndromes (17)(18)(19). Circulating AGEs likely interact with their receptor RAGE in lymphocytes, monocytes/ macrophages, and DCs that are also targets and/or reservoirs of HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the mechanism(s) involved, these perturbations result in the formation and accumulation both in blood and tissues of advanced glycation end product (AGE) molecules (10,11), a group of heterogeneous complex molecules produced by the nonenzymatic glycation between aldoses and free amino groups on proteins (12), DNA (13), or lipids (14). Elevated levels of circulating AGEs have been detected in patients with type 1 (15) and type 2 (16) diabetes, including patients infected with HIV-1 (17,18). Notably, AGEs have also been detected in patients with AIDS even in the absence of carbohydrate metabolism alteration (19).…”
mentioning
confidence: 99%
“…To our knowledge, this finding has not been reported previously and warrants further investigation. However, it should be regarded as very preliminary, since it may be due to chance and because it is difficult to determine in a study of this type whether any increased risk of mortality in those with very low A1C levels is causal or merely a result of reverse causation due to preexisting disease (23).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have highlighted a possible discordance between Hb A1c and glucose levels in treated HIV infection, suggesting Hb A1c may under-represent overall glycemia [60,61]. Evidence of low-grade hemolysis (higher mean corpuscular volume and serum haptoglobin) in HIV-infected patients with diabetes mellitus was found to predict those patients whose Hb A1c was lower than expected for glucose levels [60]. Nucleoside analogs in particular were associated with low-grade hemolysis [60].…”
Section: Case Ascertainment and Screeningmentioning
confidence: 92%
“…Evidence of low-grade hemolysis (higher mean corpuscular volume and serum haptoglobin) in HIV-infected patients with diabetes mellitus was found to predict those patients whose Hb A1c was lower than expected for glucose levels [60]. Nucleoside analogs in particular were associated with low-grade hemolysis [60]. These emerging data suggest caution in interpreting Hb A1c in treated HIV infection, particularly in patients receiving nucleoside analogs, when use of fructosamine may be indicated.…”
Section: Case Ascertainment and Screeningmentioning
confidence: 93%